Glyphosate-Modulated Biosynthesis Driving Plant Defense and Species Interactions - Fuchs Benjamin; Saikkonen Kai; Helander Marjo (Elsevier Ltd. * Trends Journals, 2022)
Glyphosate has become the best-selling herbicide used in agriculture, horticulture,
silviculture, and urban environments. It disrupts the shikimate metabolic
pathway and thereby blocks the production of aromatic amino acids, which are
the basis for several plant metabolites. Glyphosate residues are reported in
soils from diverse environments, but the effects on plant physiology and consequences
for species interactions are largely unknown. Here, we emphasize the
complexity of these physiological processes, and argue that glyphosate residues
modulate biosynthetic pathways, individually or interactively, which may affect
interactions between plants and heterotrophic organisms. In this way, glyphosate
residues can substantially interfere with plant resistance and the attraction
of beneficial insects, both of which are essential elements in integrated pest
management and healthy ecosystems.